Comparison of Maximum Stretch Forces between Femtosecond Laser-Assisted Capsulotomy and Continuous Curvilinear Capsulorhexis - Mari Takagi; Takashi Kojima; Kei Ichikawa; Yoshiki Tanaka; Yukihito Kato; Rie Horai; Akeno Tamaoki; Kazuo Ichikawa (Journal of Ophthalmology)
The current study reports comparing the postoperative mechanical properties of the anterior capsule between femtosecond laser capsulotomy (FLC) and continuous curvilinear capsulorhexis (CCC) of variable size and shape in porcine eyes. All CCCs were created using capsule forceps. Irregular or eccentric CCCs were also created to simulate real cataract surgery. For FLC, capsulotomies 5.3 mm in diameter were created using the LenSx® (Alcon) platform. Fresh porcine eyes were used in all experiments. The edges of the capsule openings were pulled at a constant speed using two L-shaped jigs. Stretch force and distance were recorded over time, and the maximum values in this regard were defined as those that were recorded when the capsule broke. There was no difference in maximum stretch force between CCC and FLC. There were no differences in circularity between FLC and same-sized CCC. However, same-sized CCC did show significantly higher maximum stretch forces than FLC. Teardrop-shaped CCC showed lower maximum stretch forces than same-sized CCC and FLC. Heart-shaped CCC showed lower maximum stretch forces than same-sized CCC. Conclusively, while capsule edge strength after CCC varied depending on size or irregularities, FLC had the advantage of stable maximum stretch forces.